2011
DOI: 10.1007/s00428-010-1031-4
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the hedgehog receptor PTCH1 in colorectal serrated adenocarcinomas is not caused by PTCH1 mutations

Abstract: Colorectal serrated adenocarcinoma forms about 15-20% of colorectal carcinomas. We have previously shown that downregulation of PTCH1 is distinctive for this type of colorectal cancer. In several other tumor types, somatic inactivating PTCH1 mutations have been shown to lead to aberrant Hedgehog signaling, but in colorectal cancer the role of PTCH1 mutations has not been thoroughly studied. Here, we have analyzed the mutation status of PTCH1 in a series of 33 colorectal serrated adenocarcinomas by sequencing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Tuppurainen et al [16 ]reported in 2005 that SAC was not directly related to microsatellite instability and Laiho et al [24] identified in 2007 the ephrin receptor B2, hypoxia-inducible factor 1-alpha and patched (PTCH1) as proteins important for the genesis of SAC. Stefanius et al [25,26 ]did not report any deleterious inactivating PTCH1 mutation in SAC but, in 2011, they observed that SAC is characterized by BRAF and KRAS mutations and it is conceivable that the loss of the PTCH1 protein expression may result from constant activation of the mitogen-activated protein kinase pathway, caused by either KRAS or BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Tuppurainen et al [16 ]reported in 2005 that SAC was not directly related to microsatellite instability and Laiho et al [24] identified in 2007 the ephrin receptor B2, hypoxia-inducible factor 1-alpha and patched (PTCH1) as proteins important for the genesis of SAC. Stefanius et al [25,26 ]did not report any deleterious inactivating PTCH1 mutation in SAC but, in 2011, they observed that SAC is characterized by BRAF and KRAS mutations and it is conceivable that the loss of the PTCH1 protein expression may result from constant activation of the mitogen-activated protein kinase pathway, caused by either KRAS or BRAF mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Stefanius et al revealed no correlation between Hh and colorectal serrated adenocarcinomas 59. Hu et al also reported that Hh signals were more frequently expressed in the microsatellite instable group, compared with the microsatellite stable group in CRC 60.…”
Section: Hh Signaling Pathway In Crcmentioning
confidence: 96%
“…Although there were studies in which 2 independent pathologists reviewed the slides, 24,33,[37][38][39][40]43,49,53 increasing the validity of the assessment, in most of the reports this information was missing 22,23,28,36,38,42,45,47,48,51 or only 1 pathologist reviewed the specimens. 32,40 The antibodies and methodological conditions used during IHC also varied significantly between studies.…”
Section: Discussionmentioning
confidence: 98%
“…In Table 2 the antibodies used for Gli1, Shh, Smo, and Ptch IHC and the positive and negative controls are summarized. 3,[22][23][24]32,33,[36][37][38][39][40][41]43,47,48,[51][52][53] Comparisons of the different antibodies is beyond the scope of this review but the effect of different antibody concentrations in the interpretation of results as been highlighted in the past. 66 In most cases the absence of primary antibody was used as a negative control but there were cases in which the primary antibody was replaced with phosphateor Tris-buffered saline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation